Carbon Nitride Enhancement for Removal of Emerging Contaminants and Pathogens through Photo-Ozonation - Fernandes, Eryk Carvalho Gomes Rodrigues (2025)
Tese de Doutoramento em Engenharia Química apresentada à Faculdade de Ciências e Tecnologia